Mapping Electoral Districts and Seat Allocation for the 2024 Elections: A Case Study of Boyolali District Election Commission (KPU): Penataan Daerah Pemilihan dan Alokasi Kursi di Kabupaten Boyolali untuk Pemilu 2024 - Pratiwi, Luvita Eska; Erowati , Dewi; Kushandajani, Kushandajani (PERSPEKTIF, 2024)
This article aims to analyze the application of the seven principles of electoral district structuring and seat allocation in the 2024 elections. The problem focuses on Electoral District Arrangement and Seat Allocation in Boyolali Regency which is experiencing the expansion of sub-district areas, from 19 sub-districts to 22 sub-districts. To approach this problem, technical guidelines for the preparation of electoral districts and allocations by the KPU of the Republic of Indonesia are used as a reference. Data was collected through interviews and literature studies of existing documents and analyzed qualitatively. This study concludes that the changes in the composition of sub-districts in electoral districts and seat allocation in Boyolali Regency have met the basic requirements for electoral district arrangement and seat allocation. These basic requirements are fulfilled by changes in population that result in the allocation of seats in one electoral district exceeding the maximum limit and/or less than the minimum limit determined by law; the expansion of the region from the original 18 sub-districts to 22 sub-districts; and there are electoral district structures and seat allocations that conflict with the principles of structuring electoral districts in previous elections which require changes and re-arrangement of the regional composition within electoral districts.